Pendampingan Masyarakat Melalui Pengajian Tematik untuk Meningkatkan Toleransi Antar Umat Islam di RW 03 Kampung Tanjungsiang - Rosenda, Diden; Saepudin, Aep; Asmaini, Nur (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This community assistance aims to increase tolerance between Muslims in RW 03 Kampung Tanjung, Tanjungsiang Village, which has around 1,200 residents who have various beliefs in schools of thought, thus hindering togetherness and tolerance. The aim of assistance is to establish Islamic Brotherhood and tolerance, minimizing divisions. The mentoring method uses interactive teaching methods through thematic recitations in the form of tabligh akbar with the title "Ukhuwah Islamiyah: The Meaning and Role of Tolerance in Maintaining the Unity and Unity of the Islamic Ummah." Successfully presenting 100 congregations, there was a significant increase in congregational interest from the usual 23 congregations. The expected results will be the basis for designing more effective sustainable religious programs, improving the quality of social relations in the community, as well as developing learning materials that are beneficial to the wider community.